Revitalizing zinc-ion batteries with advanced zinc anode design. Issue 1 (21st October 2022) - Chen, Shuwei; Wang, Huibo; Zhu, Mengyu; You, Fan; Lin, Wang; Chan, Dan; Lin, Wanxin; Li, Peng; Tang, Yuxin; Zhang, Yanyan
Abstract : This review focus on the rational design of the highly reversible zinc anode for high-performance aqueous zinc-ion batteries. The design concepts are expected to be applied to other types of high-performance aqueous energy storage systems. Abstract : Rechargeable aqueous zinc-ion batteries (AZIBs) have attracted significant attention in large-scale energy storage systems due to their unique merits, such as intrinsic safety, low cost, and relatively high theoretical energy density. However, the dilemma of the uncontrollable Zn dendrites, severe hydrogen evolution reaction (HER), and side reactions that occur on the Zn anodes have hindered their commercialization. Herein, a state-of-the-art review of the rational design of highly reversible Zn anodes for high-performance AZIBs is provided. Firstly, the fundamental understanding of Zn deposition, with regard to the nucleation, electro-crystallization, and growth of the Zn nucleus is systematically clarified. Subsequently, a comprehensive survey of the critical factors influencing Zn plating together with the current main challenges is presented. Accordingly, the rational strategies emphasizing structural design, interface engineering, and electrolyte optimization have been summarized and analyzed in detail. Finally, future perspectives on the remaining challenges are recommended, and this review is expected to shed light on the future development of stable Zn anodes toward high-performance AZIBs.